Silage quality and bacterial diversity of silages inoculated with Listeria monocytogenes and Lacticaseibacillus paracasei_6714 - Barboza Vargas, Natalia María (2023)
Introduction: King grass (Cenchrus purpureus (Schumach.) Morrone, syn. Pennisetum purpuphoides) and pineapple peel (Ananas comosus) silages are food alternatives for livestock in conditions of feed shortage. Objective: To describe the dynamics of the microbiota present in king grass and pineapple silage during the fermentation process using next generation sequencing (NGS) and to evaluate the protective effect of Lacticaseibacillus paracasei_6714 as a silage inoculum against Listeria monocytogenes. Methods: We used an unrestricted randomized design to characterize the microbiota present in silages made from king grass harvested 70 days after regrowth and pineapple peel. We inoculated mixtures of grass and peel with L. paracasei_6714 or L. monocytogenes, or both, with a non-inoculated treatment as control. The nutritional and fermentative profile was evaluated after 30 days. After 15 and 30 days of fermentation, we used 16S rRNA analysis to determine the dynamics and diversity of the microbiota in the inoculated and control silages. Result: Dry matter content and digestibility did not differ significantly; however, there were differences in crude protein, pH and organic acids. We obtained 4432 amplicon sequence variants of Proteobacteria, Firmicutes, Bacterioidetes, Actinobacteria, Verrucomicrobia, Planctomycetes and Patescibacteria. The relative abundance of each phylum varied depending on the material and fermentation period. Phylum similarity was over 70 % (but not greater than 50 % with Bray-Curtis at the species level). Conclusion: These bacterial communities seem to have an important role during silage fermentation. Proper management of silage processing can reduce or eliminate pathogenic bacteria.